Collective leadership and culture in primary schools: a comparison between the three types of schools - Koundyannan, Thiruchelvan; Abdul Kadir, Suhaida; Basri, Ramli; Mohd Ayub, Ahmad Fauzi (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study was conducted to identify the level of collective leadership and school culture in three types of schools - Sekolah Kebangsaan (SK), Sekolah Jenis Kebangsaan Cina (SJKC) and Sekolah Jenis Kebangsaan Tamil (SJKT). This study also determined the relationship between the school culture and collective leadership in primary schools and difference in collective leadership and school culture by type of schools. This is a quantitative research, involving three primary schools in Seremban, Negeri Sembilan which are SK, SJKC and SJKT. Three grade A schools located at Seremban city were chosen. A total of 90 teachers were selected as respondents - 30 teachers from each school. Data for this quantitative study was collected using the Collective Leadership Survey (Leithwood, 2008) and School Culture Survey (Gruenert, 1998) instruments. SPSS version 21 was used for the descriptive and inference data analysis. This study shows that there is high level of collective leadership and school culture prevalent in the primary schools based on SK, SJKC and SJKT school findings. The Pearson correlation analysis showed a significant correlation between collective leadership and school culture in the primary schools. The ANOVA test also showed a significant difference in collective leadership and school culture by type of schools. Collective leadership and school culture affects the effectiveness of the school and academic achievement in primary schools. The practice of collective leadership and a positive school culture can contribute to the success of a school.